Some New Refined General Boas-Type Inequalities - A. Čižmešija; J. Pečarić; D. Pokaz (Journal of Function Spaces and Applications)
We state and prove a new refined Boas-type inequality in a setting with a topological space and general σ-finite and finite Borel measures. As a consequence of the result obtained, we derive a new class of Hardy- and Pólya-Knopp-type inequalities related to balls in ℝn and prove that constant factors involved in their right-hand sides are the best possible.